Advanced Web and NetworkTechnologies, and Applications - Ishikawa, Y. (Springer, 2017)
This book constitutes the thoroughly refereed joint post-workshop proceedings of three international workshops held in conjunction with the 10th Asia-Pacific Web Conference, APWeb 2008, in Shenyang, China, in April 2008 (see LNCS 4976).